A preliminary profiling of the Paralympic powerlifting athlete: anthropometric, neuromuscular and technical correlates of performance - Rum, L.; Romagnoli, R.; Boraschi, A.; Lazich, A.; Sciarra, T.; Balletti, N.; Piacentini, M. F.; Bergamini, E. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: In Paralympic sport, the evaluation of athlete`s characteristics within the domain of performance-impairment relationship is the basis of classification to guarantee a fair competition [1]. At present, the scientific literature on Paralympic powerlifting is very limited and the evidence-based knowledge about such aspects is sparse. This study aims at understanding which factors (i.e., anthropometric, neuromuscular and technical) are related to performance to gain knowledge for evidence-based classification in this sport.